Implementation of Arabic Learning Through The Syarqi Program in The Markaz Arabiyah Pare Course - Iptikarul Ilmi; Sofyan Sauri; Nunung Nursyamsiah (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2020)
The fact of student’s enthusiasm in participating in learning Arabic in educational units, especially formal education which tends to be monotonous and lacking in designing the learning process so that the material can be conveyed properly and clearly so that the expected goals can be achieved optimally is a problem that is often heard. Considering that in arousing the enthusiasm of students so that they are happy in following Arabic lessons, one of the efforts that can be done is to teach Arabic by preparing a learning plan and teaching Arabic that is good and fun. Therefore researchers conducted further research on these matters. The purpose of this study was to determine the process of learning Arabic in non-formal institutions that prioritize aspects of language proficiency through the Shar'i program at the Pare Markaz Arabiyah Institute starting from planning, implementation, evaluation and constraints that occur in learning activities. The method used in this research is a qualitative phenomenological approach using data collection techniques in the form of observations, interviews, literature studies and documentation. The sample of this study is Arabic teachers and Syarqi class students 1. The results of the study show that: (1) The planning of learning conducted by the teacher in preparing and improving the quality of Arabic skills learning is in accordance with the guidelines for the preparation of a typical Markaz Arabiyah curriculum design. (2) The series of processes in the implementation of Arabic skills learning in terms of teaching and learning activities carried out by teachers consists of 3 series of activities, namely initial activities as preliminary, core activities and closing activities, as a whole can be assessed as good. (3) Evaluation of Arabic learning conducted by teachers is well implemented and the achievement of student evaluation results is quite satisfying. by carrying out three evaluations namely daily evaluation, weekly evaluation and final evaluation of the program, the evaluation forms that teachers use are in the form of oral tests and written tests. (4) the obstacles that occur in the process of learning Arabic are first from students who have different cognitive abilities, and from Arabic teachers who still need variations in using various learning methods, then the obstacles that arise are the lack of availability of language laboratory facilities for listening subjects.